DESIGN CONSIDERATIONS FOR A HIGH TEMPERATURE SUPERCONDUCTOR FAULT CURRENT LIMITER (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This work analyzes the functional conditions for a high-temperature superconductor (HTS) current limiter model. Introducing a superconducting fault current limiter (SFCL) in a distribution network considerably reduces the overcurrent that occurs due to a fault in the system. The analyzed SFCL conceptual model refers to a resistive limiter model, which operates on the principle of the transition of the superconducting material from the superconducting state to the resistive state when one of the critical parameters of the superconducting state is exceeded, such as the critical current (Ic). Thus, with the occurrence of a fault current for I > Ic, the superconductor goes into a resistive state (phenomenon called "quench") and the current will be diverted to an alternative resistive circuit. The parameters of the quench are analyzed for different current values (50, 100, 200, and 300 A) to determine the protection sizing and operation of an SFCL. They are investigated through numerical simulations with Comsol Multiphysics.
Keywords: Fault current limiter; Design; Superconductor; Quench; Numerical simulations